A history of Denmark - Jespersen, Knud J. V. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"Knud Jespersen traces the historical roots of the modern Danish state and Denmark's international position. This revised, updated and expanded new edition features additional material on issues such as the Danish church, the Enlightenment, cultural history, World War II, current NATO debates and the 2006 "cartoon crisis." "--
Machine generated contents note: -- Acknowledgements -- Maps of Denmark -- Introduction: What is Denmark and Who are the Danes? -- Foreign and Security Policy: From Gatekeeper of the Baltic to a Midget State -- Domestic Policy, 1500-1848: The Era of Aristocracy and Absolutism -- Domestic Policy, 1848-2000: Democracy and the Welfare State -- The Church and Culture from Luther to Postmodernism -- Economic Conditions: The Old Denmark, 1500-1800 -- Economic Conditions: The New Denmark, 1800-2010 -- The Danes: A Tribe or a Nation? -- Notes -- Select Bibliography -- A Short Chronology -- Index.
Includes bibliographical references (p. 241-245) and index.
Keywords: HISTORY / Europe / Scandinavia; HISTORY / Social History; HISTORY / Europe / General; Denmark -- History